2020
DOI: 10.1177/0363546519895242
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Outcomes After Intra-articular Injection With Adipose-Derived Cultured Stem Cells or Noncultured Stromal Vascular Fraction for the Treatment of Knee Osteoarthritis: Response

Abstract: The authors declared that they have no conflicts of interest in the authorship and publication of this contribution. AOSSM checks author disclosures against the Open Payments Database (OPD). AOSSM has not conducted an independent investigation on the OPD and disclaims any liability or responsibility relating thereto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The original study was a prospective cohort study which investigated the effects of three different AMSC dose injections [63]. Out of the studies, 16 were prospective [43,49,[62][63][64][65][66][67][68][69][70][71][72][73] and two were retrospective [74,75]. Only five were randomised controlled trials [48,49,64,[69][70][71][72].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The original study was a prospective cohort study which investigated the effects of three different AMSC dose injections [63]. Out of the studies, 16 were prospective [43,49,[62][63][64][65][66][67][68][69][70][71][72][73] and two were retrospective [74,75]. Only five were randomised controlled trials [48,49,64,[69][70][71][72].…”
Section: Resultsmentioning
confidence: 99%
“…AMSCs were positive for CD73, CD90. AMSCs were negative for CD31, CD34, CD45 Nakamura et al (2019) [75] 12.75 × 10 6 cells, unknown for SVF…”
Section: Abdomen Liposuctionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, under appropriate culture conditions, stem cells can be expanded in vitro while maintaining their chondrogenic potential [ 16 ]. Several studies have demonstrated the efficacy of intra-articular (IA) injection of cultured BMSCs in promoting healing of chondral defects, not only in preclinical animal studies, but also in pilot human clinical trials [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%